Association of COVID-19-related perceptions and experiences with depression and anxiety in Ugandan caregivers of young children with malaria and iron deficiency: A cross-sectional study. - Saeun Park; Paul Bangirana; Ezekiel Mupere; Reagan I Baluku; Erika S Helgeson; Sarah E Cusick (PLoS ONE)
Background Caregivers of young children may have been particularly vulnerable to mental health challenges during the COVID-19 pandemic due to its negative impacts on their housing, finances, and childcare demands. This study explored the associations between COVID-19-related experiences and symptoms of depression and anxiety among Ugandan caregivers. Methods This cross-sectional study included 100 Ugandan caregivers of young children aged 6-59 months with uncomplicated malaria and iron deficiency (N = 85) and without malaria or anemia (N = 15) who were enrolled in the Optimizing Iron Status in Malaria-Endemic Areas (OptiM) study. Sociodemographic data and COVID-19 experiences were collected using an internally developed survey and symptoms of depression and anxiety were measured using the Hopkins Symptom Checklist (HSCL-25) and the Center for Epidemiologic Studies Depression (CESD-20) scale. Multiple linear regression models were used to assess the associations between COVID-19 survey scores with HSCL-25 or CESD-20 scores. Results Nearly half of caregivers reported clinically meaningful symptoms of depression (46%) and/or anxiety (49%). Caregivers had more severe symptoms of depression and/or anxiety if they experienced greater changes in living situations or decreases in physical activity (CESD-20: β = 3.35, 95% CI [1.00, 5.70], p = .01), food insecurity (HSCL-25: β = 3.25, 95% CI [0.41, 6.10], p = .03, CESD-25: β = 3.09, 95% CI [0.79, 5.39], p = .01), and domestic violence (HSCL-25: β = 3.82, 95% CI [0.94, 6.70], p = .01) during COVID-19. These associations did not vary depending on whether the caregivers had children with malaria. Conclusions Negative COVID-19 experiences were significantly associated with more severe depression and anxiety in Ugandan caregivers, regardless of their children's malaria status. Urgent attention and action are needed to support the mental well-being of this vulnerable population. Further prospective studies should investigate the long-term impact of COVID-19 on caregivers and their children.